A New Difference Sequence Set of Order α and Its Geometrical Properties - Mikail Et; Vatan Karakaya (Abstract and Applied Analysis)
We introduce a new class of sequences named as mαΔr,ϕ,p and, for this space, we study some inclusion relations, topological properties, and geometrical properties such as order continuous, the Fatou property, and the Banach-Saks property of type p.